Leveraging Social Media for Strategic Business Excellence in Wine Tourism: Insights from China’s Helan Mountains - Cao , Chaoyi; Ramachandran, Sridar; Siow, May Ling; Liu, Huijuan; Wang, Zhenbin (Journal of Ecohumanism, 2025)
Purpose: The main purpose of this study was to fill the research gap regarding the factors influencing the decision-making intentions of wine tourists through social media and explore the mediating effect of emotional attitude in this relationship. Approach: The study was conducted in two stages. First, significant social media factors influencing the ’decision-making intention’ among wine tourists were identified. Then, the mediating role of ’emotional attitude’ between social media influence and ’decision-making intention’ was explored. Findings: The study found that ’ource credibility’, ’opinion leaders’, ’number of electronic Word of Mouth (eWOM)’, and ’information attractiveness’ have a considerable impact on the ’decision-making intention’ through the mediating effect of ’emotional attitude’. Additionally, it was noted that the ’number of eWOM’ is the most significant factor. Value: This study is the first to integrate all these constructs into a single model and empirically test it, providing valuable insights for the application of social media in the wine tourism sector. It also highlights the managerial, social, and academic implications of the research.